2007
DOI: 10.1007/bf03033565
|View full text |Cite
|
Sign up to set email alerts
|

The 6-Hydroxydopamine model of parkinson’s disease

Abstract: The neurotoxin 6-hydroxydopamine (6-OHDA) continues to constitute a valuable topical tool used chiefly in modeling Parkinson's disease in the rat. The classical method of intracerebral infusion of 6-OHDA involving a massive destruction of nigrostriatal dopaminergic neurons, is largely used to investigate motor and biochemical dysfunctions in Parkinson's disease. Subsequently, more subtle models of partial dopaminergic degeneration have been developed with the aim of revealing finer motor deficits. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
276
2
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(291 citation statements)
references
References 149 publications
(98 reference statements)
7
276
2
6
Order By: Relevance
“…This kind of effect proves that the 6-hydroxydopamine toxication is the ideal animal model for PD studies [25,26]. The levels of glucose, triglycerides, and protein were estimated, and we found significant alteration between the control, lesion and treated group.…”
Section: Discussionsupporting
confidence: 62%
“…This kind of effect proves that the 6-hydroxydopamine toxication is the ideal animal model for PD studies [25,26]. The levels of glucose, triglycerides, and protein were estimated, and we found significant alteration between the control, lesion and treated group.…”
Section: Discussionsupporting
confidence: 62%
“…When neuron deterioration reaches such levels, compensation mechanisms are insufficient to contain deficits, leading to the manifestation of initial PD motor symptoms (Simola, Morelli, & Carta, 2007).…”
Section: Parkinson's Disease Characteristicsmentioning
confidence: 99%
“…The primary adopted techniques include genetic manipulation and, more frequently, neurotoxininduced dopamine depletion (Meredith et al, 2008;Simola et al, 2007).…”
Section: Proprioceptive Deficits In Animal Models Of Parkinson's Diseasementioning
confidence: 99%
“…Animal models, based on the toxic damage induced by the neurotoxin 6-hydroxydopamine (6-OHDA) are used extensively for accurately mimicking aspects of human PD in rats [13]. Although the precise mechanism underlying 6-OHDA-induced area-specific neuronal damage occurs remains to be ascertained, studies making use of the 6-OHDA rat model have shown repeatedly that this involves mitochondrial functional impairment [14]. For instance, 6-OHDA has been shown to generate iron-dependent oxidative stress and deplete antioxidant (e.g., glutathione) levels, while it was also reported that 6-OHDA inhibits complexes I and IV of the mitochondrial electron transport chain (METC) [15,16].…”
Section: Experimental Toxins Support a Role For Mitochondrial Patholomentioning
confidence: 99%